Zachowania autodestrukcyjne i suicydalne adolescentów jako odpowiedź na problemy egzystencjalne - Ćwikliński, Andrzej (Kultura-Społeczeństwo-Edukacja, 2023)
The article deals with the issue of self-destructive and suicidal behaviors of adolescents as a response to their existencial problems. Behavior of this type among young people is a big problem for both the people they concern and the people who organize help for tchem. There are many stressors in adolescence. Their source may be relationships with a close person, experience of loss, experience of abuse or humiliation by a caregiver or partner difficulties in school, work, sports or other activities as well as direct or media contacts with people, most often peers, who also display self-destructive behaviors. The study uses the lecture method based on the literature on the subject. The analysis of sources and scientific studies shows that the problem of self-destructive and suicidal behaviours among adolescents increases as a result of unfavourable living conditions and the lack of access to appropriate medical care.